Respuesta :
Answer:
[tex]b=0\: or\: b=4[/tex]
Step-by-step explanation:
The given equation is [tex]\frac{5}{3b^3-2b^2-5}=\frac{2}{b^3-2}[/tex]
By cross multiplication, we get;
[tex]5(b^3-2)=2(3b^3-2b^2-5)[/tex]
We expand to get:
[tex]5b^3-10=6b^3-4b^2-10[/tex]
Combine like terms to get:
[tex]6b^3-5b^3-4b^2-10+10=0[/tex]
[tex]b^3-4b^2=0[/tex]
Factor to get:
[tex]b^2(b-4)=0[/tex]
This implies that:
[tex]b=0\: or\: b=4[/tex]
Answer:
C. b = 0 and b = 4
Step-by-step explanation:
What is the solution for the equation StartFraction 5 Over 3 b cubed minus 2 b squared minus 5 EndFraction = StartFraction 2 Over b cubed minus 2 EndFraction?
b = –4 and b = 0
b = –4
b = 0 and b = 4
b = 4